Do politically connected directors affect accounting quality? Evidence from China's anti-corruption campaign (Rule 18) - HOPE, Ole-Kristian (Institutional Knowledge at Singapore Management University, 2017)
We examine the impact of politically connected directors on accounting quality using a quasi experiment in China. In October 2013, “Rule 18” was issued to prohibit government and party officials, who were concurrently holding public offices or had recently retired from such positions within the last three years, from serving as directors for publicly listed firms. The regulation is part of China’s anti-corruption campaign, and it has led to a large number of politically connected directors resigning from their roles as directors involuntarily. As such, Rule 18 has effectively weakened, if not fully discontinued, the political connections of the firms that previously hired government officials as directors. Our empirical analyses employ a difference-in-differences research design with firm fixed effects to examine the pre- and post- period accounting quality around the enactment of Rule 18. We find that, compared to propensity-score-matched control firms, the accounting quality of firms with politically connected directors increases after Rule 18, and that the effect is stronger for non-state-owned enterprises firms than for state-owned enterprises firms. We further examine the channels through which politically connected directors affect accounting quality. The evidence suggests that connected firms have better access to preferential financing and are under lax regulations, which reduce firms’ incentives to provide transparent information.